Religious Ceremonies in the Oasis of Bukhara (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Every ethnic group, nation has its own independent, unique and unique culture. The regional and historical specificity of people's life creates conditions for the development of the culture of each people, nation, and nation. In the article, the religious rituals in the Bukhara oasis were analyzed and studied from an ethnographic point of view.